Enhanced 3He 4He ratios and cosmogenic helium in ultramafic xenoliths - Porcelli, DR; Stone, J; O'Nions, R (1987)
Recently erupted ultramafic xenoliths generally have ratios of 3He 4He = (5-10) × RA, which are similar to the values characterizing mid-ocean ridge basalts (MORB). During the course of additional investigations of ultramafic xenoliths, samples from several locations have been found with 3He 4He ratios of either whole rock or mineral separates that are substantially higher than those found in MORB, up to over 400 × RA. These elevated ratios correspond to 3He excesses of between 8·10-14 and 2·10-12 cm3 STP g-13He, assuming that the samples initially contained He with an isotopic composition similar to that of MORB and other xenoliths from the sample localities. These excesses are consistent with a derivation from in situ cosmic-ray spallation, considering the production rates for the particular latitudes, altitudes, and exposure ages involved. These results demonstrate that cosmogenic He identified in samples from Maui can be found in significant quantities in other geological samples that have been used to characterize mantle He. © 1987.